Analisis Sterilisasi Jus Kunyit Skala Komersil: Pendekatan HTST dan PEF - Apriliawan, Hadi (Buletin Ilmiah Impas, 2025)
Turmeric (Curcuma longa L.)is a multifunctional plant, functional food and its production is quite high in Indonesia, but turmeric processing is very limited and the shelf life of processed products in the form of juice is low so it is easily damaged. This study aims to evaluate the combined application of Pulsed Electric Field (PEF) and Low Temperature Long Time (LTLT) treatment for producing turmeric juice that effectively eliminates microorganisms while preserving the color, aroma, and nutritional content of the final product. The goal is to achieve a commercially sterile turmeric juice in compliance with the Indonesian National Standard (SNI). Two sterilization methods were tested: (1) LTLT followed by PEF, and (2) High Temperature Short Time (HTST) followed by PEF. The Total Plate Count (TPC) after treatment was 3.0 × 10⁴ CFU/mL. The most effective method for meeting SNI sterility standards was the HTST + PEF combination, with a TPC of 0.3 × 10⁴ CFU/mL achieved at 75°C for 9 seconds. The HTST + PEF method demonstrated superior effectiveness in producing turmeric juice that meets commercial sterility standards while maintaining product quality. This study provides an efficient and practical approach for communities and industry to process turmeric juice using rapid methods that ensure safety, retain quality, and comply with SNI standards.